Basic Food Groups’ Consumption Pattern Among Pregnant Women: Food Consumption Among Pregnant Women (Journal of Food and Dietetics Research, 2023)
Objective: The objective of this study was to find out the 5 Basic Food Groups’ Consumption Pattern Among Pregnant Women in the study area. Methodology: This research employed descriptive survey design. The respondents were pregnant women who have pregnancies between 2 to 40 weeks and within the age range of 15 to 30 years and above. Four Hundred (400) pregnant women were selected using simple random sampling techniques to constitute the research sample. Questionnaires were directly distributed in the area of study, specifically to the pregnant women. The collected data was analyzed using simple frequency percentage. Results: The majority of women (44%) reported consuming three meals per day, followed by those who eat more than 3 meals per day (42%). Only14% of the pregnant women eat less than 3 meals per day. 4% of the study population eat fruits every day, whereas, 32% of them never eat fruits. Those that eat vegetables every day, carried the highest percentage (72%), followed by those that eat vegetables sometimes (28%). Those that eat grains daily carried the highest percentage (86%), followed by those that eat grains sometimes (14%). Those that eat protein foods sometimes carried the highest percentage (64%), with only 28% of them who eat protein foods every day. Those that never eat dairy foods carried the highest percentage (50%), followed by those who eat dairy foods sometimes (34%), with only 16% of the pregnant women who eat dairy foods daily. Conclusion: It can be concluded from the results that the majority of the study subjects did not have an adequate intake pattern for the 5 basic food groups.
Keywords: Malnutrition; Food groups; dietary diversity; gestation period; consumption pattern